42 : the Jackie Robinson story - Helgeland, Brian; Boseman, Chadwick; Ford, Harrison, 1942-; Beharie, Nicole (Burbank, CA : Warner Home Video, 2013)
Depicts the early career of Jackie Robinson as he became the first African American Major League Baseball player when he was signed to the 1947 Brooklyn Dodgers.
Originally released as a motion picture in 2013.
Features: Stepping into history; UltraViolet digital copy.
Chadwick Boseman, Harrison Ford, Nicole Beharie, Christopher Meloni, Ryan Merriman.
MPAA rating: Not rated.
DVD, Dolby digital 5.1.
In English, French, or Spanish with optional French or Spanish subtitles.
Keywords: Robinson, Jackie, -- 1919-1972 -- Drama; Brooklyn Dodgers (Baseball team) -- Drama; Major League Baseball (Organization) -- Drama; African American baseball players -- Drama; Baseball players -- United States -- Drama; Race discrimination -- United States -- History -- 20th century -- Drama; African Americans -- Social conditions -- History -- 20th century -- Drama; Sports films; Fiction films; Video recordings for the hearing impaired; Feature films; Biographical films